Profil Kemampuan Koneksi Matematis Murid Berkemampuan Rendah dalam Menyelesaikan Soal Teorema Pythagoras - Mochamad Ibnu Humam Arief; Mulyono (FKIP Universitas Mataram, 2026)
Mathematical connection ability is a fundamental competency that Indonesian students have not yet developed optimally, as evidenced by persistently low performance on both national and international assessments. This condition warrants in-depth qualitative investigation, particularly among low-achieving students whose specific connection difficulties remain poorly understood. This qualitative descriptive study was conducted at SMA Negeri 3 Semarang. A total of 72 tenth-grade students completed a preliminary written test measuring three NCTM mathematical connection indicators. Based on the results, ten students fulfilling at most one indicator were selected through purposive sampling as interview subjects. Data from semi-structured interviews were analyzed using the Miles and Huberman model. Results revealed nine subjects fulfilled only Indicator 1, one fulfilled only Indicator 2, and none fulfilled Indicator 3. Interview exploration revealed distinct thinking processes across all three indicators and three qualitative patterns of connection difficulty comprising weak prerequisite mastery, inability to link concepts that were individually understood, and inability to complete problem-solving despite having a sense of the solution path. These findings highlight the importance of diagnostic and instructional approaches tailored to the specific nature of each student's difficulty.